3-6/5x = -3 X=__

1 answer

To solve the equation \( \frac{3 - 6}{5x} = -3 \), we first simplify the left side:

  1. Simplify \( 3 - 6 \): \[ 3 - 6 = -3 \]

  2. Substitute this back into the equation: \[ \frac{-3}{5x} = -3 \]

  3. To eliminate the fraction, multiply both sides by \( 5x \) (assuming \( x \neq 0 \)): \[ -3 = -3 \cdot 5x \]

  4. Simplify the right side: \[ -3 = -15x \]

  5. Now, divide both sides by -15: \[ x = \frac{-3}{-15} \]

  6. Simplify the fraction: \[ x = \frac{1}{5} \]

So the value of \( x \) is \( \frac{1}{5} \).